Soil depths and microhabitats shape soil and root-associated bacterial and archaeal communities more than crop rotation in wheat - Giongo, Adriana; Arnhold, Jessica; Grunwald, Dennis; Smalla, Kornelia; Braun-Kiewnick, Andrea (Frontiers in Microbiomes, 2024)
The plethora of microorganisms inhabiting the immediate vicinity of healthy root systems plays a pivotal role in facilitating optimal nutrient and water acquisition by plants. In this study, we investigated the soil microbial communities associated with wheat roots within distinct microhabitats, root-affected soil (RA), rhizosphere (RH), and rhizoplane (RP). These microhabitats were explored at five soil depths, and our investigation focused on wheat cultivated in a monoculture (WM) and wheat crop rotation (WR). Overall, there were significant differences in microbiota composition between WM and WR, although no difference in bacterial diversity was observed. Differentially abundant taxa between WM and WR were observed in all three microhabitats, emphasizing important insights on the localization of commonly associated bacteria to wheat roots. Comparing the microhabitats, RP exhibited the most dissimilar microbial composition in WM and WR. Taxa that were differentially abundant between WM and WR were observed in the three microhabitats. The high relative abundance of taxa belonging to the phylum Proteobacteria in the rhizoplane, such as Devosia, Pseudomonas, Shinella, and Sphingomonas, along with other genera, such as Pedobacter (Bacteroidota), Agromyces and Streptomyces (Actinobacteriota) highlight the recruitment of potentially beneficial bacterial taxa to the vicinity of the roots. Interestingly, these taxa were observed along the entire length of wheat roots, even at depths of up to 120 cm. The presence of specific taxa associated with wheat roots at all soil depths may be beneficial for coping with nutrient and water shortages, particularly under upcoming climate scenarios, where water may be a limiting factor for plant growth. This study provides valuable insights for designing management strategies to promote a diverse and healthy microbial community in wheat cropping systems, considering soil depth and microhabitats as key factors. Although, at this time, we cannot link specific bacterial taxa to yield reductions commonly observed in monocultural fields, we propose that some genera may enhance plant nutrient or water acquisition in rotation compared with monoculture. Advanced technologies, including functional analyses and culturomics, may further enhance our understanding of the ecological roles played by these microbes and their potential applications in sustainable agriculture.